Does job insecurity keep employees from the organisation? - Karcika, Oykum; Bozkurt, Serdar; Demirhan, Ayse (INDERSCIENCE ENTERPRISES LTD, 2025)
Along with the global economic imbalances, the rising trend of unemployment rates and the deterioration of working conditions cause employees to experience fear regarding potential job loss at any given time. The behavioural consequences of this situation, job insecurity (JI), which can harm organisations, remain essential in today's business world and organisational behaviour literature. In this direction, it is intended to test the role of work-family conflict (WFC) in the relationship between employees' perceptions of JI and organisational citizenship behaviour (OCB) based on social exchange and diffusion theories. Data obtained from 251 participants working in the private sector were analysed using the partial least squares (PLS) program. Because of the research, it was seen that WFC partially mediates the relationship between JI and OCB.
Keywords: job insecurity; organisational citizenship behaviour; OCB; work-family conflict; WFC; social exchange theory; SET; PARTIAL LEAST-SQUARES; CITIZENSHIP BEHAVIOR; MEDIATING ROLE; PLS-SEM; SATISFACTION; COMMITMENT; PERFORMANCE; VALIDATION; SECURITY; Business & Economics